The Concept of Professional Competence and its Relevance to Language Teaching Methods (Eurasian Scientific Herald, 2023)
The functionality and effectiveness of the complex of psychological, pedagogical and organizational and pedagogical conditions proposed in this article in the process of teaching a foreign language to students in various situations, their verbal understanding, assessment, expression, regulation with a focus on development and increasing communicative competence as an integral element of professional training in a pedagogical university, in order to significantly increase educational motivation, to contribute to the professional development of the future teacher